Pengaruh Return On Asset (ROA) Terhadap Profitabilitas PT ANEKA TAMBANG Tbk (ANTAM) Berdasarkan Laporan Keuangan Periode 2020-2024 - Wulandari, Erin Sinarsih; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2025)
Financial report is a report that shows the current financial condition of a company or within a certain period of time. This study focuses on PT Aneka Tambang Tbk (ANTAM), one of the leading companies in the Indonesian mining sector. The purpose of this study is to see the effect of Return On Asset (ROA) on the Profitability of PT Aneka Tambang (ANTAM) based on financial reports from 2020 to 2024. This study uses the Descriptive Statistics method, with the population studied being the financial reports of PT Aneka Tambang (ANTAM) from 2020 to 2024. The data collection technique for this study uses the Pearson Correlation Test Results and Simple Linear Regression Tests. The results of this study indicate that Return On Asset (ROA) plays an important role in how much the company manages assets to generate profits in the period 2022 to 2024 even though financial performance varies. However, the analysis shows that the relationship between total assets and ROA is not statistically significant. This confirms that to increase profitability, companies must concentrate on effective and efficient management strategies in the use of assets and consider other elements that can affect financial performance, such as market conditions and good financial management.